Escuta Dicótica em Indivíduos com e sem doença de Alzheimer - Araújo , Aline Menezes Guedes Dias de (2015)
Alzheimer disease is defined by a gradual disappearance of memory and other cognitive functions. Essential information on the auditory perception of the patient, from the implementation of behavioral hearing tests, may contribute to the differential diagnosis between AD and other alterations typical of aging. This study aimed to investigate the relationship between auditory perception and Alzheimer disease. A systematic review on the subject and an empirical: two articles were developed. The final sample consisted of the systematic review of 14 articles. After this review study of selected articles, it was found that 21.42% related hearing and Alzheimer disease, pointing to the diversity of behavioral hearing tests that can be used in this population. The second article of the empirical study was attended by 18 seniors, 12 without Alzheimer disease and 6 with the disease. They were submitted to pure tone and speech audiometry and auditory processing evaluation by two behavioral tests: dichotic alternating disyllable test and the dichotic digits test. There was asymmetry of the ears both in non-competitive condition as competitive in the dichotic alternating disyllable test, and the worst results were found in the left competitive in both groups mainly on the competitive left the group with Alzheimer. It was also observed that both dichotic tests showed similar results. The use of central auditory tests can aid in the diagnosis of Alzheimer disease and contribute to understanding the changes that occur in central auditory function during the aging process.